Who is in favor of enlargement? Determinants of support for EU membership in the candidate countries' referenda - Orla Doyle; Jan Fidrmuc (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2004)
We analyze support for EU membership as expressed in voting patterns in the candidate countries' referenda on EU membership, using regional referendum results and individual survey data on voting intentions. We find that favorable individual and regional characteristics are positively correlated with support for accession and voter participation. In contrast, those who should benefit from future EU transfers are less likely to vote and/or support EU membership. We argue that voters in the candidate countries assign greater weight on future benefits from liberalization and integration than on potential gains through redistribution.
Keywords: J61; P26; P33; Z13; 330; Voting; referendum; EU enlargement; integration